2004
DOI: 10.1037/h0088893
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review of Play Therapy Assessments.

Abstract: As part of the creative modalities, play therapy offers a therapeutic mode far diagnosis, assessment, and treatment interventions. The purpose of this paper is to critically review three play therapy interventions:The Developmental Play Assessment, the Marschak Interaction Method, and the Family Systems Test. A brief introduction to each assessment will be presented. Additionally, validity and reliability data will be addressed. The overall evaluation will include the assessments desirable as well as undesirab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The child’s play ability, as an outcome measure, is rarely used in play therapy even though play is the natural mode for children (Bratton, Ray, Rhine, & Jones, 2005; Phillips, 1985). One play assessment used in play therapy as an outcome measure is the Developmental Play Assessment (Brooke, 2004). This assessment was reviewed by Brooke (2004) who concluded that his assessment was standardized on a small sample of children diagnosed with autism and so its application to the wide range of children referred to play therapy is limited.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The child’s play ability, as an outcome measure, is rarely used in play therapy even though play is the natural mode for children (Bratton, Ray, Rhine, & Jones, 2005; Phillips, 1985). One play assessment used in play therapy as an outcome measure is the Developmental Play Assessment (Brooke, 2004). This assessment was reviewed by Brooke (2004) who concluded that his assessment was standardized on a small sample of children diagnosed with autism and so its application to the wide range of children referred to play therapy is limited.…”
mentioning
confidence: 99%
“…One play assessment used in play therapy as an outcome measure is the Developmental Play Assessment (Brooke, 2004). This assessment was reviewed by Brooke (2004) who concluded that his assessment was standardized on a small sample of children diagnosed with autism and so its application to the wide range of children referred to play therapy is limited. Children's pretend play (also called fantasy play, representational play, make-believe play, and imaginative and symbolic play) has been of interest to play therapists because theorists who have placed emphasis on the long term benefits of play have encouraged pretend play in therapy (Howe & Silvern, 1981).…”
mentioning
confidence: 99%
See 3 more Smart Citations